2016
DOI: 10.5851/kosfa.2016.36.5.594
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Microbial Level for Livestock Products in Retail Meat Shops Implementing HACCP System

Abstract: This study aimed to examine the microbial contamination levels in livestock products at retail stores. Beef, pork, and chicken samples from raw materials and final products were obtained between January and December 2015. All homogenized meat samples (25 g) were tested for the aerobic plate count (APC), coliform count (CC), and Escherichia coli count (E. coli). The highest APCs in meat samples, by month, at retail shops were obtained in September, followed by July, May, and October (p<0.001). However, APC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 12 publications
(18 reference statements)
2
26
4
2
Order By: Relevance
“…On the contrary, Kim and Yim [24] reported the lower prevalence of aerobic bacteria plate count lower, in which all samples had aerobic bacteria plate count lower than 1×10 6 CFU/g. All city slaughterhouses in this study had an average TPC lower than 1×10 6 CFU/g with mean value of 0.26×10 6 CFU/g.…”
Section: Resultsmentioning
confidence: 98%
“…On the contrary, Kim and Yim [24] reported the lower prevalence of aerobic bacteria plate count lower, in which all samples had aerobic bacteria plate count lower than 1×10 6 CFU/g. All city slaughterhouses in this study had an average TPC lower than 1×10 6 CFU/g with mean value of 0.26×10 6 CFU/g.…”
Section: Resultsmentioning
confidence: 98%
“…Health status of butcher shop workers, cloths and knives, wooden boards, and weighing scales can act as a source of microbial contamination (Abebe et al, 2019;Ali et al, 2010). A great diversity of microbes inhabits fresh meat generally, but different types may become dominant depending on pH, composition textures, storage temperature, and transportation means of raw meat (Adu-Gyamfi et al, 2012) The microbial quality and safety of raw meat products can be estimated by the use of indicator microorganisms, including total aerobic plate count, coliform count and Escherichia coli count (Kim and Yim, 2016). The microbiological contamination of meat can occur during processing and manipulation, such as skinning, evisceration, storage and distribution at slaughter houses.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also showed that for each microbiological criterion, a large variability was observed between the minimum and maximum values recorded (Table ). This variability is likely due to the diversity of sampling sites since the examined samples were neither processed from the same raw pork, nor from the same processing environment, and hygiene and handling practices greatly vary from one processor to another, as previously reported (Anihouvi et al, ; Carrasco, Morales‐Rueda, & García‐Gimeno, ; Kim, Hur, & Yim, ; Kim & Yim, ; Manios et al, ).…”
Section: Resultsmentioning
confidence: 90%